Small animal soft tissue surgery - Monnet, Eric (John Wiley & Sons, Ltd., 2023)
"Small Animal Soft Tissue Surgery, Second Edition offers a thoroughly revised new edition of this comprehensive, detailed reference to surgical syndromes and diseases in small animal patients. Featuring detailed surgical descriptions accompanied by high-quality illustrations, the book updates the procedures throughout to include new and revised techniques. New chapters cover pyloric hypertrophy, coagulation factors and anticoagulation strategies, and pacemakers, with a newly standalone chapter on persistent aortic arches. Organized by body system, each section of the book includes a brief review of surgical anatomy and physiology. Chapters present surgical techniques, with information on pathophysiology, diagnosis, treatment, and prognosis, and a companion website provides video clips and slideshows demonstrating the procedures. Relying on the very latest literature to present the current state of the art, Small Animal Soft Tissue Surgery is an essential reference for small animal surgeons, residents, and practitioners performing soft tissue surgery"--